1994
DOI: 10.1254/jjp.66.451
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by Ascorbic Acid 2-Glucoside or Repeated Additions of Ascorbate of Mitogen-Induced IgM and IgG Productions by Human Peripheral Blood Lymphocytes

Abstract: ABSTRACT-In this study, the effect of ascorbic acid 2-glucoside (AA-2G), a stable derivative of ascorbic acid (AsA), or repeated additions of ascorbate on antibody productions by human peripheral blood lym phocytes (PBLs) was examined, and the physiological function of AsA was evaluated. When human PBLs were stimulated with Staphylococcus aureus Cowan I or pokeweed mitogen, AA-2G remarkably increased the numbers of IgM and IgG-secreting cells which were detected by enzyme-linked immunospot assay. Although a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…The role of vitamin C within these cells is less clear, although antioxidant protection has been suggested [ 194 ]. In vitro studies have indicated that incubation of vitamin C with lymphocytes promotes proliferation [ 76 , 77 ], resulting in enhanced antibody generation [ 78 ], and also provides resistance to various cell death stimuli [ 195 ]. Furthermore, vitamin C appears to have an important role in developmental differentiation and maturation of immature T-cells ( Table 1 ) [ 76 , 79 ].…”
Section: Vitamin C and Leukocyte Functionmentioning
confidence: 99%
“…The role of vitamin C within these cells is less clear, although antioxidant protection has been suggested [ 194 ]. In vitro studies have indicated that incubation of vitamin C with lymphocytes promotes proliferation [ 76 , 77 ], resulting in enhanced antibody generation [ 78 ], and also provides resistance to various cell death stimuli [ 195 ]. Furthermore, vitamin C appears to have an important role in developmental differentiation and maturation of immature T-cells ( Table 1 ) [ 76 , 79 ].…”
Section: Vitamin C and Leukocyte Functionmentioning
confidence: 99%
“…Recent research has indicated that vitamin C treatment attenuates synthesis of the pro-inflammatory cytokines TNF, IL-6, and IL-1β [ 57 ]. In vitro studies suggest that ascorbic acid operates as potent immunostimulator of antibody production (IgM and IgG) in humans and that the intracellular ascorbic acid content is a key parameter for establishing the immune response of peripheral blood lymphocytes [ 58 ]. Other in vitro studies have shown the role of vitamin C in promoting T-cell maturation [ 59 ].…”
Section: Vitamin Cmentioning
confidence: 99%
“…The same finding was observed in elderly women treated with a higher dose of vitamin C and vitamin E for longer period: 1 g vitamin C daily plus 200 mg of vitamin E for 16 weeks [ 44 ]. An in vitro evidence showed that vitamin C increased production of immunoglobulins by peripheral blood lymphocytes [ 51 ]. Moreover, vitamin C supplement of 200 mg/day for 1–3 months increased IgG and IgM serum levels and improved humoral immune response in elderly [ 43 ].…”
Section: Immunomodulatory Effect Of Vitamin Cmentioning
confidence: 99%